The Effect of Work-life Balance on Accounting Ethics - Cem Berk; Fatih Gundogmus (6th International OFEL Conference on Governance, Management and Entrepreneurship. New Business Models and Institutional Entrepreneurs: Leading Disruptive Change. April 13th - 14th, 2018, Dubrovnik, Croatia, 2018)
Work-life balance is gaining importance as people get more difficult duties both at home and work. Accounting professionals work in a stressful environment where their private life might have effect on work performance and unethical behavior. Some of the important works in the literature find out that accounting ethics classes should exist and include more case studies than theory, accounting ethics should be inserted throughout the whole university curriculum teaching to achieve moral values by easy to understand examples even by human intuitions. The goal should be to develop values and virtues of accounting professionals, the accounting ethics standards should be principle based rather than rule based, accounting ethics problems may lead to financial crisis, accounting professionals with leader role perceive the institution environment more ethical, and financial ratios can be used in detecting earning manipulation. For this study, a survey is conducted for members of members of Istanbul Chamber of Certified Accountants, Turkey. The #of respondents is 380. The methodology used in the research is a regression. During the research, the effect of work-life balance on ethical behavior is analyzed to test the main hypothesis that there is a relationship between work-life balance and not behaving against accounting ethics. Four different independent variables which are parts of work-life balance are also analyzed whether they are significant in explaining ethical behavior of accountants. Based on the results, the main hypothesis is statistically accepted. The effect of personal life to work doesn't affect ethical behavior, whereas the effect of work to personal life, work-life growth and the effect of working with husband/wife of other relative affect ethical behavior. Work-life growth has a positive and the others have a negative impact. Moreover, the differentiation of work-life balance based on gender, age, education and marital status in these four independent variables are tested. Based on the results in all of the regressions, differentiation is detected. Some selected findings revel that, women have more work-life balance problem, age group 56 and more experiences more problems due to the effect of personal life to work and work to personal life, master's or higher education group has a significantly higher work-life growth than higher education, and married people have more effect of work to personal life.The differentiation analysis for accounting ethics is also given again based on gender, age, education and marital status but in three personal characteristics of the respondents. Some of the selected findings include that women, age group 36-45, vocational education, and married groups behave more ethically, university education group is more responsible, and age group 46-55 has less honesty, reliability, and objectivity than 30-35, 36-45 and 56 and more age groups. In Turkey, it is suggested that only occupational institution should be responsible for accepting principles, standards and regulations on accounting ethics. Accounting ethics should be taught during accounting education and also during the career such as seminars, conferences and in-service education by the occupational institution.
Keywords: 650; Work-life balance; Accounting ethics; Personal life; Accounting profession